THE TENTH GRADERS’ PERCEPTION OF THE EFFECTIVENESS OF PROJECT-BASED LEARNING TO IMPROVE ENGLISH WRITING SKILL - Ikfina Khoirun Nisa; Hartono . (Jurnal Ilmiah Sultan Agung, 2023)
The purpose of this study was to gather empirical data on how the 10th-grade students at SMA Islam Sultan Agung 01 Semarang felt about the effectiveness of project-based learning in enhancing their English writing abilities. This research is of the qualitative variety. The population of this study consisted of 10th-grade students who had taken classes using a project-based learning approach and an autonomous curriculum. Six students made up the sample in this study, including two high achievers, two average achievers, and two below average achievers. Interviews were the primary method of gathering data. The researcher looked about the school before the interview. Project-based learning is one of the approaches that students prefer, according to the research findings. The project-based learning approach is quite successful. Keywords: students’ perception, writing skill, project-based learning